Delaying cord clamping until ventilation onset improves cardiovascular function at birth in preterm lambs. (19th March 2013) - Bhatt, Sasmira; Alison, Beth J.; Wallace, Euan M.; Crossley, Kelly J.; Gill, Andrew W.; Kluckow, Martin; te Pas, Arjan B.; Morley, Colin J.; Polglase, Graeme R.; Hooper, Stuart B.
Key points Delayed cord clamping improves circulatory stability in preterm infants at birth, but the underlying reason is not known. In a new preterm lamb study we investigated whether delayed cord clamping until ventilation had been initiated improved pulmonary, cardiovascular and cerebral haemodynamic stability. We demonstrated that ventilation prior to cord clamping markedly improves cardiovascular function by increasing pulmonary blood flow before the cord is clamped, thus further stabilising the cerebral haemodynamic transition. These results show that delaying cord clamping until after ventilation onset leads to a smoother transition to newborn life, and probably underlies previously demonstrated benefits of delayed cord clamping. Abstract Delayed cord clamping improves circulatory stability in preterm infants at birth, but the underlying physiology is unclear. We investigated the effects of umbilical cord clamping, before and after ventilation onset, on cardiovascular function at birth. Prenatal surgery was performed on lambs (123 days) to implant catheters into the pulmonary and carotid arteries and probes to measure pulmonary (PBF), carotid (CaBF) and ductus arteriosus blood flows. Lambs were delivered at 126 ± 1 days and: (1) the umbilical cord was clamped at delivery and ventilation was delayed for about 2 min (Clamp 1st; n = 6), and (2) umbilical cord clamping was delayed for 3–4 min, until after ventilation was established (Vent 1st; n = 6). All lambs were subsequently ventilated for 30 min. In Clamp 1st lambs, cord clamping rapidly (within four heartbeats), but transiently, increased pulmonary and carotid arterial pressures (by ∼30%) and CaBF (from 30.2 ± 5.6 to 40.1 ± 4.6 ml min−1 kg−1), which then decreased again within 30–60 s. Following ventilation onset, these parameters rapidly increased again. In Clamp 1st lambs, cord clamping reduced heart rate (by ∼40%) and right ventricular output (RVO; from 114.6 ± 14.4 to 38.8 ± 9.7 ml min−1 kg−1), which were restored by ventilation. In Vent 1st lambs, cord clamping reduced RVO from 153.5 ± 3.8 to 119.2 ± 10.6 ml min−1 kg−1, did not affect heart rates and resulted in stable blood flows and pressures during transition. Delaying cord clamping for 3–4 min until after ventilation is established improves cardiovascular function by increasing pulmonary blood flow before the cord is clamped. As a result, cardiac output remains stable, leading to a smoother cardiovascular transition throughout the early newborn period.